The effect of genetic background on behavioral manifestation of Grid2(Lc) mutation - Cendelin, Jan; Tuma, Jan; Korelusova, Ivana; Vozeh, Frantisek (Behavioural brain research, 2014)
Mutant mice are commonly used models of hereditary diseases. Nevertheless, these mice have phenotypic traits of the original strain, which could interfere with the manifestation of the mutation of interest. Lurcher mice represent a model of olivocerebellar degeneration, which is caused by the Grid2(Lc) mutation. Lurchers show ataxia and various cognitive and behavioral abnormalities. The most commonly used strains of Lurcher mice are B6CBA and C3H, but there is no information about the role of genetic background on the Grid2(Lc) manifestation. The aim of this work was to compare spatial navigation in the Morris water maze, spontaneous activity in the open field and motor skills on the horizontal wire, slanted ladder and rotarod in B6CBA and C3H Lurcher mutant and wild type mice. The study showed impaired motor skills and water maze performance in both strains of Lurcher mice. Both C3H Lurcher and C3H wild type mice had poorer performances in the water maze task than their B6CBA counterparts. In the open field test, C3H mice showed higher activity and lower thigmotaxis. The study showed that genetic backgrounds can modify manifestations of the Lurcher mutation. In this case, B6CBA Lurcher mice models probably have more validity when studying the behavioral aspects of cerebellar degeneration than C3H Lurcher mice, since they do not combine abnormalities related to the Grid2(Lc) mutation with strain-specific problems.
Keywords: Rotarod Performance Test; bludiště - učení; Cerebellar degeneration; Receptors, Glutamate; Female; glutamátové receptory; Ataxia; Mutation; vnímání prostoru; Maze Learning; myši; Mice, Inbred C3H; Olivopontocerebellar Atrophies; myši - mutanty neurologické; Mice; mutace; Species Specificity; motorické dovednosti; myši inbrední C3H; druhová specificita; Disease Models, Animal; Motor Skills; olivopontocerebelární atrofie; mužské pohlaví; Space Perception; zvířata; nemoci mozečku; ženské pohlaví; metoda rotující tyčky; Genetic background; Cerebellar Diseases; Animals; Mice, Neurologic Mutants; Male; Spatial orientation; modely nemocí na zvířatech; Lurcher mice